Perancangan E-Commerce Berbasis Web Pada Toko Tas Brandes Leather Menggunakan Metode Prototype - I Kadek Adi Sanjaya Putra Sanjaya; Putri Anugrah Cahya Dewi (Primakara University, 2021)
Utilization of the web today can also be used for trading activities such as E-Commerce. E-Commerce is used by traders to facilitate the sale of a product and process transactions. During this pandemic, E-Commerce is very necessary. During this pandemic, people were more interested in shopping online, according to the latest annual report from the solution-commerce startup, Sirclo, entitled